Synthesis and Characterization of Grewia asiatica-Stabilized Silver Nanoparticle as a Selective Probe for Al+3 in Tap, Deionized, Industrial Waste Water and Human Blood Plasma - Nasreen Begum; Itrat Anis; Shazia Haider; Tabinda Zarreen Mallick; Muhammad Iqbal Chaudhary (Journal of Chemistry)
Aluminum can be found in water and vegetables in the form of the trivalent ion (Al3+), which can potentially contaminate food and water. Overconsumption of aluminum can lead to serious health problems in humans. Therefore, there is a need for an economical and simple procedure to detect the presence of aluminum. In this study, we synthesized a conjugate of Grewia asiatica extract with silver nanoparticles. The nanoparticle-stabilized fruit extract of Grewia asiatica was found to be an extremely selective sensor of Al3+ in tap water, DI water, industrial wastewater, and human blood plasma. We characterized the Grewia asiatica-conjugated silver nanoparticles (GA-AgNPs) using UV-visible, SEM, and AFM techniques and found that they were stable in an extensive pH range and different electrolyte concentrations up to 10 M NaCl. The GA-AgNPs were circular in shape with typical particle sizes of 65–97 nm. We inspected the photo physical properties of GA-AgNPs concerning metallic ions using UV-visible spectroscopy and found that they were highly selective for Al3+ ions, with no interfering ions detected in competitive experimentation. The absorption intensity of GA-AgNPs was directly related to Al3+ concentration over a wide range of concentrations (6.25–500 μM). Jobs plot experiment displayed 1 : 1 binding stoichiometry between GA-AgNPs, and Al3+. Additionally, GA-AgNPs were effectively utilized for the recognition of Al3+ in laboratory tap water, DI water, industrial wastewater, and human blood plasma.